2014
DOI: 10.3390/s140305354
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Users, Context and Devices for Ambient Assisted Living Environments

Abstract: The participation of users within AAL environments is increasing thanks to the capabilities of the current wearable devices. Furthermore, the significance of considering user's preferences, context conditions and device's capabilities help smart environments to personalize services and resources for them. Being aware of different characteristics of the entities participating in these situations is vital for reaching the main goals of the corresponding systems efficiently. To collect different information from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The developers have to take into consideration many aspects of data corruption resulted from the remote acquisition, the delay of collection and the obstacles of timing. The uncertainty of the used devices and the criticality of the wearable ones are influencing factors for the data reliability and certainty [18]. Therefore, choosing the appropriate collection technology is forced by the structure of the environment and the other concepts related to the context extraction.…”
Section:  Data Providersmentioning
confidence: 99%
“…The developers have to take into consideration many aspects of data corruption resulted from the remote acquisition, the delay of collection and the obstacles of timing. The uncertainty of the used devices and the criticality of the wearable ones are influencing factors for the data reliability and certainty [18]. Therefore, choosing the appropriate collection technology is forced by the structure of the environment and the other concepts related to the context extraction.…”
Section:  Data Providersmentioning
confidence: 99%
“…"In clinical settings ICF is used for functional status assessment, goal setting, treatment planning and monitoring, as well as outcome measurement" (WHO -ICF, 2001). ICF represents a valuable starting point to identify patients' disabilities and functioning conditions (Castillejo et al, 2014a;2014b).…”
Section: Usability Concerns: Patients' Functional Disabilitiesmentioning
confidence: 99%
“…It is thus observed that, from product design to multimedia and user interfaces adaptation, the approaches described above, even though the collected personal data characteristics to improve the system and user's satisfaction and product or service usability differ a lot, share the same goal. For a more extended review, the reader is directed to [23].…”
Section: Related Workmentioning
confidence: 99%